Proceedings of the Interaction Design and Children Conference 2020
DOI: 10.1145/3392063.3394433
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative comic-based digital storytelling with primary school children

Abstract: This work explores how comic-based digital storytelling can support primary school children in reflecting on situations involving conflict in the classroom. In particular, we focus on investigating three specific aspects: (1) the potential of digital story composition conducted collaboratively or individually, (2) the children's perception on the use of digital storytelling for reflecting on conflicts that might arise in class and, (3) the teachers' experience of introducing a digital tool for collaborative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…Children also engaged in media literacy and narrative thinking when putting together content using the DST. Motivated by the collaborative possibilities of DST, Rutta al (Rutta et al, 2020).…”
Section: Learning With Digital Storytellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Children also engaged in media literacy and narrative thinking when putting together content using the DST. Motivated by the collaborative possibilities of DST, Rutta al (Rutta et al, 2020).…”
Section: Learning With Digital Storytellingmentioning
confidence: 99%
“…366) "family stories affect and reflect family culture by communicating who a family is, its norms, its values, its goals, its identity." Moreover, past research on DSTs has together shown the importance of collaborative and negotiated meaning making that children engage in whilst crafting stories with their peers [e. g., (Rubegni & Landoni, 2014) (Rutta et al, 2020) (Di Blas et al, 2010). The important role of stories in "making family" on the one hand, and the collaborative opportunities of making stories with others using DST on the other, motivates the focus of this work on DST and the family.…”
Section: Introductionmentioning
confidence: 99%
“…This aligns with the opinion of Mioramalala et al (2021) who stated that media suited to students' conditions would facilitate learning. One type of media that can be used as technology-based learning media is e-comic (Mansur et al, 2023;Rutta et al, 2020). E-comic is a learning medium connected to the internet, with an output in the form of a link that can be accessed using digital media with a single click (Swandi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating technology, digital storytelling can provide a dynamic and interactive learning experience for students, making it a popular choice among teachers (Tanrikulu, 2022;Yang et al, 2022). Kervin and Mantei (2016) and Rutta et al (2020) found that digital storytelling had a positive impact on 8-year-old children's reflection and construction of science knowledge. The results suggest that digital storytelling can be an effective tool for promoting student learning and engagement in science education.…”
Section: Introductionmentioning
confidence: 99%